Motivasi Dan Komunikasi Dalam Pengembangan UMKM Di Desa Jatisura - Widayani Wahyuningtyas; Sintha Fransiske; Ruri Firliani; Ibnu Malkan Bakhrul Ilmi (IKRA-ITH ABDIMAS, 2023)
Motivation and communication are important in making movement. Especially in Jatisura Village whichhas abundant agricultural products. Based on this, the researcher sees that the produce in Jatisura Village canbe an opportunity and be developed through the efforts of local residents through UMKM. So the idea arose toconduct research. The research was conducted in Jatisura Village. The purpose of this study was to determine themotivation and communication in the development of UMKM in Jatisura Village. The research method used isdescriptive qualitative method, with data collection namely observation, interviews and documentation studies.The results of interviews conducted by researchers, respondents include housewives, housewives whobecome or farmers, housewives who are entrepreneurs and business people. Respondents who do businesssuch as mango crackers, mango seed coffee, mango juice, shredded cork fish, knitting, selling in school canteensand basic food stores. The results of the research that have been carried out show that the people of JatisuraVillage who have motivation and communication can develop UMKM. Meanwhile, the people of JatisuraVillage who do not have motivation and communication cannot develop UMKM. The motivations that existinclude internal and external. Communication also determines the success of UMKM